1380 Occupational risk factor for lymphatic or haematopoietic cancer: case-control study using occupational cancer monitoring system data. (24th April 2018) - Park, SM; Leem, JH; Kim, HC
Abstract : Introduction: According to 2011 annual report of national cancer registration program, age-standardised incidence of non-hodgkin lymphoma, leukaemia, multiple myeloma, Hodgkin lymphoma is 6.8, 5.0, 1.4, 0.5 per 1, 00, 000. Although incidence rate is low, social attention is increasing due to the fatality. While there has been many foreign studies on association between occupational risk factor and lymphatic, haematopoietic cancer, a study reflecting the domestic situation is insufficient. So we conducted case-control study using data from occupational cancer monitoring system to assess risk factor. Methods: Cases were 384 leukaemia, 523 non-hodgkin lymphoma, 218 multiple myeloma patients reported from occupational cancer monitoring system from 2011 to 2014. Controls were selected randomly matched on age, sex, residence. All participants were interviewed for lifestyle habits, exposure or occupational history of group1, group2A carcinogen. Analysis was performed using chi-square test primarily, and logistic regression to adjust for smoking status. Results: Analysing by chi-square test, excess risks were shown for exposure to benzene, formaldehyde, TCE, PAH in leukaemia, to benzene, formaldehyde, TCE in non-hodgkin lymphoma, to benzene, formaldehyde in multiple myeloma. Analysing by logistic regression to adjust for age, sex, smoking status, excess risk were shown for exposure to benzene, formaldehyde, pesticide in non-hodgkin lymphoma, to benzene in multiple myeloma. Other exposures were associated with lymphatic or haematopoietic cancer, but were not significant. Conclusion: Increased risk of lymphatic or haematopoietic cancer were associated with some occupations and chemicals. But other exposures showed no statistically significant association due to insufficient number of samples. There is a need for sufficient number of samples to obtain additional association between exposure and cancer risk.